Mindfulness Exercises: A Key to Reducing Stress in Adult Volleyball Athletes - Qori Nur Hijah; Muhamad Tafaqur; Ridha Mustaqim (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Adult volleyball athletes often experience high pressure from both internal and external sources. This causes adult athletes to be prone to prolonged stress. If not treated immediately, this can cause them difficulty in achieving their maximum performance. This study aims to examine the effect of mindfulness training in reducing stress in adult volleyball athletes. This study used a quantitative approach with an experimental method involving 8 adult male volleyball athletes aged 17-25 years in Bandung Regency. The instrument used was the Perceived Stress Scale (PSS 10) questionnaire, which was administered before and after the mindfulness training treatment. The results showed that mindfulness training significantly reduced stress levels in adult volleyball athletes. The results of this study showed a significance value of 0.00, which is smaller than 0.05. In conclusion, mindfulness training has been shown to reduce stress among adult volleyball athletes and can serve as a reference for psychological training programs during daily training to help manage stress.